2006
DOI: 10.1002/app.25079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PVAc bonding on finger‐joint strength of steamed and unsteamed beech wood (Fagus sylvatica)

Abstract: Beech wood is one of the most important species used in furniture production in Europe. In this work, the effects of poly(vinyl acetate) (PVAc) bonding [durability classes D1, D2, and D3 according to EN 204 : 2001), finger length (4 and 10 mm), and finger orientation on the bending strength of finger-jointed steamed and unsteamed beech wood (Fagus sylvatica) were studied. Specimens were prepared according to EN 385 (2001) In both steamed and unsteamed wood the specimens with a finger length of 10 mm showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 3 publications
0
11
1
Order By: Relevance
“…Vassiliou et al (2007) reported that MOE of finger jointed samples of Beechwood joined using 10 mm long fingers and PVA was found unaffected compared to clear samples. The good retention of MOE of finger jointed African hardwood sections using resorcinol-formaldehyde adhesive up to about 83-98 % of the individual clear sections depending on the wood density and with a finger length of 18 mm also has been reported (Ayarkwa et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Vassiliou et al (2007) reported that MOE of finger jointed samples of Beechwood joined using 10 mm long fingers and PVA was found unaffected compared to clear samples. The good retention of MOE of finger jointed African hardwood sections using resorcinol-formaldehyde adhesive up to about 83-98 % of the individual clear sections depending on the wood density and with a finger length of 18 mm also has been reported (Ayarkwa et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Even the samples with finger length of 14 mm were still inferior to those achieved in this study. Finger joints glued with PVAc adhesive were also studied by Vassiliou et al (2007), where samples of Fagus sylvatica wood were subjected to bending tests. Class D1 and D2 adhesives showed lower modulus of rupture, while for the class C adhesive the modulus of rupture value was higher than that of adhesive D4 analyzed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the finger length from 4 to 15 mm caused an increase in the mean modulus of rupture values. The effects of three durability classes of polyvinyl acetate bonding and of two finger lengths (4 mm and 10 mm) on the bending strength of steamed and unsteamed beech wood have been studied (Vassiliou et al 2007). It was found that higher modulus of rupture values resulted from the 10-mm finger length.…”
Section: Introductionmentioning
confidence: 99%